2002
DOI: 10.1002/ijc.10890
|View full text |Cite
|
Sign up to set email alerts
|

Does skin fibroblast radiosensitivity predict squamous cancer cell radiosensitivity of the same individual?

Abstract: Individualization of radiation doses is presumed to result in better radiotherapy outcome. Success rate in measuring radiosensitivity is probably the most limiting factor for present radiosensitivity assays to be introduced into clinical routine. To find a simpler predictive parameter, we compared the radiosensitivity of dermal fibroblasts and head and neck squamous cell carcinoma (SCC) cell lines established from the same individuals. The radiosensitivity was tested using the clonogenic 96-well plate assay. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Three human SCCHN cell lines were utilized: FaDu (hypopharyngeal squamous carcinoma; American Type Culture Collection), UT-SCC-8 and UT-SCC-42a (laryngeal squamous cell carcinoma); the latter two lines were a generous gift from R. Grenman (Department of Otorhinolaryntology-Head and Neck Surgery, University of Turku, Finland) [23]. FaDu cells were maintained in Minimum Essential Medium, supplemented with 10% Fetal Bovine Serum (FBS), 1.5 g/L bicarbonate, and 1 mM pyruvate.…”
Section: Methodsmentioning
confidence: 99%
“…Three human SCCHN cell lines were utilized: FaDu (hypopharyngeal squamous carcinoma; American Type Culture Collection), UT-SCC-8 and UT-SCC-42a (laryngeal squamous cell carcinoma); the latter two lines were a generous gift from R. Grenman (Department of Otorhinolaryntology-Head and Neck Surgery, University of Turku, Finland) [23]. FaDu cells were maintained in Minimum Essential Medium, supplemented with 10% Fetal Bovine Serum (FBS), 1.5 g/L bicarbonate, and 1 mM pyruvate.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the tumor heterogeneity may increase the actual a/b value, 42,131 and the use of homogeneous models overestimates its statistical significance. 132 If some studies suggest some correlation between in vitro and in vivo parameters, [133][134][135][136][137][138][139][140][141] in others little or no correspondence is achieved between in vitro predictions and relevant clinical endpoints. [141][142][143][144][145][146] This lack of correlation may be due to small patient sample sizes, unreliable radiosensitivity indicators, or uncertain relationship among in vitro indicators and in vivo endpoints.…”
mentioning
confidence: 99%
“…Some of the genetic factors involved in the radiosensitivity of normal oral mucosa are likely to be shared with oral squamous cell carcinoma, as the present study showed that the response of oral cancer to radiochemotherapy correlated with the susceptibility of normal oral mucosa to the therapy in many cases. In addition, the radiosensitivity of normal skin fibroblasts is reported to correlate with that of squamous carcinoma cells in the same individual 4 .…”
Section: Discussionmentioning
confidence: 98%